Inhibition of Calmodulin-Dependent Kinase Kinase Blocks Human Cytomegalovirus-Induced Glycolytic Activation and Severely Attenuates Production of Viral Progeny - McArdle, Jessica (American Society for Microbiology (ASM), 2011)
Viruses depend on the host cell to provide the energy and biomolecular subunits necessary for production of viral progeny. We have previously reported that human cytomegalovirus (HCMV) infection induces dramatic changes to central carbon metabolism, including glycolysis, the tricarboxylic acid (TCA) cycle, fatty acid biosynthesis, and nucleotide biosynthesis. Here, we explore the mechanisms involved in HCMV-mediated glycolytic activation. We find that HCMV virion binding and tegument protein delivery are insufficient for HCMV-mediated activation of glycolysis. Viral DNA replication and late-gene expression, however, are not required. To narrow down the list of cellular pathways important for HCMV-medicated activation of glycolysis, we utilized pharmaceutical inhibitors to block pathways reported to be both involved in metabolic control and activated by HCMV infection. We find that inhibition of calmodulin-dependent kinase kinase (CaMKK), but not calmodulin-dependent kinase II (CaMKII) or protein kinase A (PKA), blocks HCMV-mediated activation of glycolysis. HCMV infection was also found to target calmodulin-dependent kinase kinase 1 (CaMKK1) expression, increasing the levels of CaMKK1 mRNA and protein. Our results indicate that inhibition of CaMKK has a negligible impact on immediate-early-protein accumulation yet severely attenuates production of HCMV viral progeny, reduces expression of at least one early gene, and blocks viral DNA replication. Inhibition of CaMKK did not affect the glycolytic activation induced by another herpes virus, herpes simplex virus type 1 (HSV-1). Furthermore, inhibition of CaMKK had a much smaller impact on HSV-1 replication than on that of HCMV. These data suggest that the role of CaMKK during the viral life cycle is, in this regard, HCMV specific. Taken together, our results suggest that CaMKK is an important factor for HCMV replication and HCMV-mediated glycolytic activation.